2015
DOI: 10.1080/19443994.2015.1012121
|View full text |Cite
|
Sign up to set email alerts
|

Development of bioreactor systems for decolorization of Reactive Green 19 using white rot fungus

Abstract: immobilized fungi by approximately 80%, which is a twofold improvement over decolorization without mediators. In bioreactor system, decolorization of Reactive Green 19 was increased to 82% after 72 h. We evaluated the efficiency of the decolorization model for use in a small industry. Our results indicated that the wastewater discharge of 10 m 3 d −1 requires a reactor volume of 24 m 3 to obtain 80% decolorization with a retention time of 1.75 d. This study identifed that bioreactor of T. versicolor U97 immobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
1
3
0
1
Order By: Relevance
“…Previously, it has reported that RG19, which is the same as in our study, was decolorized by whiterot species Cordyceps militaris MTCC3936 (Kaur et al 2015), white rot fungal species Trametes versicolor (Sari et al 2016) and saline-pH tolerant fungus Pestalotiopsis sp. strain NG007 (Yanto et al 2014).…”
Section: Indicator Color Plate Testssupporting
confidence: 83%
“…Previously, it has reported that RG19, which is the same as in our study, was decolorized by whiterot species Cordyceps militaris MTCC3936 (Kaur et al 2015), white rot fungal species Trametes versicolor (Sari et al 2016) and saline-pH tolerant fungus Pestalotiopsis sp. strain NG007 (Yanto et al 2014).…”
Section: Indicator Color Plate Testssupporting
confidence: 83%
“…This reaction occurs in an acid medium (pH~3) to allow the decomposition of the hydrogen peroxide into hydroxyl free radicals acting as strong oxidants [96]. Other types of Fenton techniques are also applicable such as electro-Fenton, photo-Fenton and sono-Fenton, with the possibility of a combination of them [97]. Interestingly, the acid yellow 17 [79], Basic violet 3 [87] and Amido black 10B [118] dyes were treated by the Fenton oxidation process.…”
Section: Oxidationmentioning
confidence: 99%
“…Recent developments in various bioreactors like fluidized beds and rotating biological contactors have been applied for bioremediation with immobilized fungi [14]. Novel bioreactor systems are continuously being designed for the removal of dyes like Reactive Green 19 by white-rot fungi [127]. A two stage reactor was successful in degradation azo dye Reactive Blue 222 through combination of Photo-Fenton's and aerobic treatment with two white-rot fungi P. ostreatus IBL-02 and P. chrysosporium IBL-03 [128].…”
Section: Technological Advances In Fungal Bioremediationmentioning
confidence: 99%